A comprehensive review on secondary metabolites and health-promoting effects of edible lichen. (May 2021) - Zhao, Yingshu; Wang, Mingfu; Xu, Baojun
Graphical abstract: Highlights: Edible lichens have been used as ethnic food in different societies. Lichens contain enormous secondary metabolites. Active substances from lichens possess multiple health benefits. Lichens could provide new options for R & D of novel functional foods. Abstract: Lichens have been concerned by many researchers because of their unique secondary metabolites. However, the research on edible lichens is still lacking. This review collected the applications of lichens in food, analyzed the nutritional values and edible values of lichens, and summarized the potential health benefits of lichens. These may provide new options for the development and research of novel functional foods and/or drugs. The literature on lichens all came from library databases and electronic retrieval systems, including PubMed, Science Direct, Scopus, Google Scholar, and CNKI. Lichens have been proven to have theoretically rich nutritional value, and their extracts and active substances have also been shown to have multiple health benefits including anti-cancer, anti-inflammation, anti-oxidative stress, and anti-diabetes. However, the bioavailability of nutrients derived from lichens, the mechanism of action of their bioactive substances is still unclear. These may be the future directions of lichen research.